The conserved fibroblast growth factor receptor–based signaling is required for dendrite regeneration - Pallavi Singh; Mydhily Vasudevan; Swagata Dey; Kavinila Selvarasu; Supraja Balakrishnan; Dikshalee Bassi; Anindya Ghosh-Roy (Proceedings of the National Academy of Sciences, 2026)
Both axons and dendrites of a neuron are susceptible to physical insults during stroke and trauma. Unlike axon regeneration, the mechanisms of dendrite regeneration remain largely elusive. In this study, we developed a high-throughput method to induce dendrite injury in the PVD neuron of Caenorhabditis elegans , enabling systematic analysis of regenerative mechanisms. We combined this efficient injury method with RNAi to screen through 825 genes that are highly expressed in PVD neurons. We identified key regulators of dendrite regeneration, including the fibroblast growth factor receptor (FGFR) EGL-15 and its downstream signaling components, regulators of F-actin dynamics, and transcription factors. Moreover, our findings indicate that FGFR/EGL-15 is both necessary and sufficient within the neuron at an early point after injury to initiate branching from the broken dendrite tip, and it is also required in the epidermal tissue to prevent the distal dendrite degeneration. Further analysis revealed that the FGF ligand, EGL-17, functions within the surrounding epithelia for the neuron-specific role of EGL-15. Downstream of EGL-15, the GRB2/SEM-5 adaptor-dependent signaling arm involving GEF/SOS-1, RAS/LET-60, and MAPK-1/MPK-1 is required for dendrite regeneration. In summary, our study identified the conserved FGFR signaling that responds to dendrite injury to initiate dendrite regeneration. Our screening also identified pathways involving F-actin dynamics and transcription factors, which will help the dissection of the dendrite regeneration mechanism in the future.